Antifungal Efficacy of Amphotericin B in Candida Albicans Endocarditis Therapy: Systematic Review - Bezerra,Lucas Soares (2020)
Abstract Introduction: Although it is the most common agent among the fungal causes of endocarditis, Candida albicans endocarditis is rare. Objective: To evaluate the efficacy of amphotericin B in the treatment of C. albicans endocarditis beyond a systematic review. Data search: Articles in English, Spanish and Portuguese, conducted in the following databases: MEDLINE, LILACS, IBECS and SciELO, in humans and published in the last 25 years. Study selection: Observational studies, clinical trials, and case series providing data on the amphotericin B use in patients with a C. albicans endocarditis diagnosis without age limitations. Data synthesis: From the initial search (n=79), 25 articles were fully evaluated, of which 19 were excluded for meeting one or more exclusion criteria, remaining five articles (two observational studies and three case series). Patients using amphotericin B demonstrated improvement in survival rates, and its main use was in association with the surgical method as well as with caspofungin association. Conclusion: Literature lacks evidence to conclude about efficacy and safety of amphotericin B in the treatment of fungal endocarditis. Randomized clinical trials are necessary to provide better evidence on the subject.